ATMOSPHERIC TOURISMMELALUI PENGATURAN AMENITAS SEBAGAI DAYA DUKUNG PARIWISATA BERKELANJUTAN DI BALI - Tarunajaya, Wisnu Bawa (JURNAL KEPARIWISATAAN, 2011)
Atmospheric tourism can be created by how we arrange, place, manage, layout, physical facilities. Whether good or bad atmospheric is created, depends on our ability to harmonize arrange physical facilities with our achieved goals and on the role of local government. In the beginning. that local government regulation was created to bring a peaceful and enjoyable condition, as Bali has a stable development in the tourist industry. Occasionally there were some changes in practice. Most of the buildings are built without considering the reguÂlation and as a consequence, it creates a bad, noisy traffic jam especially at some points. It would be better. it all stakeholders are concerned to create a good atmospheric and harmonization in all aspects. As Bali is an a-small-attracÂtive island, it needs one management and one plan, so that we can ensure its sustainable tourism development.